Lernersprachliche Texte im Biologieunterricht eine Analyse von Versuchsprotokollen von Schülerinnen und Schülern mit Deutsch als Erst- und Zweitsprache - Ricart Brede, Julia (De Gruyter Mouton, 2020)
The book presents a corpus analysis of experimental protocols written by students in 8th grade biology classes. The main corpus consists of 332 protocols by students with German as their first or second language, and the ancillary corpus contains "ideal student protocols" written by the teachers. The data reveal that texts written students with German as their first language also reflect language-learner features
Keywords: Beschreiben; Deutsch als Zweitsprache; Erklären; Experiment protocol; German as second language; Versuchsprotokoll; description; explanation; LANGUAGE ARTS & DISCIPLINES / Linguistics / General; Textproduktion; Fremdsprache; Deutsch; Biologieunterricht; Hochschulschrift